Enhancing Chemistry Education Through The Integration of Rote Ndao Cultural Practices: An Ethnographic Exploration of Ethnochemistry - Ardyansyah, Ananta (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
This study explores how integrating local cultural practices into chemistry education through ethnochemistry can provide a practical and relevant solution to these challenges. Conducted in Oeseli Village, a seven-day ethnographic study employed observations, interviews, and documentation to identify culturally significant products, such as Rote sugar, sopi (a traditional alcoholic beverage), and fried milk. These products were found to align with key chemistry concepts, including organic chemistry, fermentation, and particle interactions. By embedding these cultural assets into the chemistry curriculum, educators can enhance student engagement, contextualize learning, and overcome barriers imposed by the lack of traditional laboratory resources. The findings highlight the potential for using local traditions to foster a deeper understanding of chemistry while promoting science education that is both accessible and culturally relevant in remote regions like Rote Ndao. This approach encourages the development of a sustainable, localized educational model that can be adapted to other marginalized communities facing similar educational constraints.